Detection of enterotoxin and toxic shock syndrome toxin 1 genes in Staphylococcus, with emphasis on coagulase-negative staphylococci - Cunha, Maria de Lourdes R. S. da [UNESP]; Calsolari, Regina A. O. [UNESP]; Araújo Jr., João Pessoa [UNESP] (Wiley, 2007)
The detection of staphylococcal enterotoxins is decisive for the confirmation of an outbreak and for the determination of the enterotoxigenicity of strains. Since the recognition of their antigenicity, a large number of serological methods for the detection of enterotoxins in food and culture media have been proposed. Since immunological methods require detectable amounts of toxin, molecular biology techniques represent important tools in the microbiology laboratory. In the present study, polymerase chain reaction (PCR) was used to identify genes responsible for the production of enterotoxins and toxic shock syndrome toxin 1 (TSST-1) in S. aureus and coagulase-negative staphylococci (CNS) isolated from patients and the results were compared with those obtained by the reverse passive latex agglutination (RPLA) assay. PCR detection of toxin genes revealed a higher percentage of toxigenic S. aureus strains (46.7%) than the RPLA method (38.3%). Analysis of the toxigenic profile of CNS strains showed that 26.7% of the isolates produced some type of toxin, and one or more toxin-specific genes were detected in 40% of the isolates. These results suggests the need for further studies in order to better characterize the pathogenic potential of CNS and indicate that attention should be paid to the toxigenic capacity of this group of microorganisms.
Keywords: Coagulase-negative staphylococci; Enterotoxins; PCR; TSST-1; coagulase; enterotoxin; toxic shock syndrome toxin 1; agglutination test; bacterial strain; gene identification; nonhuman; polymerase chain reaction; Staphylococcus; Staphylococcus aureus; Staphylococcus epidermidis; Staphylococcus haemolyticus; Staphylococcus hominis; Staphylococcus lugdunensis; Staphylococcus simulans; staphylococcus warneri; Staphylococcus xylosus; toxin analysis; Coagulase; Nucleic Acid Hybridization; Polymerase Chain Reaction; Staphylococcal Infections